Physical performance differences between spanish selected and nonselected para-footballers with cerebral palsy for the national team - Peña-González, I.; Sarabia, J. M.; Roldan, A.; Manresa-Rocamora, A.; Moya-Ramón, M. (International Journal of Sports Physiology and Performance, 2021)
In regular football, the players` selection process involves an objective assessment based on their anthropometric and physical performance. However, available literature focused on players` selection process in cerebral palsy (CP) football is scarce.